Differential photosynthetic performance and photoprotection mechanisms of three Mediterranean evergreen oaks under severe drought stress - Javier Peguero-Pina, Jose; Sancho-Knapik, Domingo; Morales, Fermín; Flexas, Jaume; Gil-Pelegrín, Eustaquio (FUNCTIONAL PLANT BIOLOGY, 2009)
The ability of three Mediterranean oaks (Quercus coccifera L., Quercus ilex ssp. ballota (Desf.) Samp and Quercus suber L.) to cope with intense drought was investigated. Water stress reduced stomatal conductance and photosynthesis in these species. Drought-mediated changes in photosynthetic-related parameters allowed the characterisation of the specific photo-protective mechanisms. Specifically, Q. suber downregulated photosynthetic electron transport rates (ETR) closing PSII reaction centres (i.e. decreasing photochemical quenching) and through an antheraxanthin (A) + zeaxanthin (Z)-mediated diminished intrinsic PSII efficiency (Phi(exc.).). These changes were lower in Q. coccifera and Q. ilex ssp. ballota, which decreased further ETR photo-inactivating PSII centres (evidenced by their low predawn F(v)/F(m) ratios at high water stress). The predawn F(v)/F(m) ratio decreased in Q. coccifera largely due to F(m) decreases, whereas in Q. ilex ssp. ballota F(v)/F(m) decreases were due to F(0) increases, below -4 MPa. These F(v)/F(m) decreases were well correlated with increases in the A + Z photo-protective pigments. An analysis of dark respiration and photorespiration as alternative electron sinks under intense drought stress also revealed interspecific differences. The largest imbalance between electrons generated and consumed increased potentially oxidative damage in Q. suber. Subsequently, only Q. suber showed loss of chlorophyll, which is one of the main targets of oxidative damage. Data suggest that Q. coccifera and Q. ilex ssp. ballota seem more able than Q. suber to withstand highly xeric conditions. Therefore, our results question the consideration of Mediterranean evergreen oaks as a homogeneous physiological group.
Keywords: morphological convergence; photoprotection; physiological performance; Quercus; Summer aridity; water stress

Climatic discrimination of Mediterranean broad-leaved sclerophyllous and deciduous forests in central Spain - Gavilán, Rosario; Fernández-González, Federico (Journal of Vegetation Science, 1997)
Abstract. Climatic differences between three types of deciduous (Quercus pyrenaica) and three types of sclerophyllous (Quercus rotundifolia) Mediterranean forests in the Spanish Sistema Central were analyzed by means of Canonical Discriminant Analysis and Jancey's Discriminant Analysis, applied in successive steps to data from 252 meteorological stations. Climatic data included temperature and precipitation records as well as bioclimatic indices. Discriminant analysis was applied to broad-leaved sclerophyllous and deciduous forest communities sampled at each meteorological station using phytosociological methods. Annual and seasonal (summer, spring) water availability are the most important factor controlling the distribution of the two physiognomic forest types; southwestern associations of Quercus pyrenaica and Q. rotundifolia differ from their colder homologues by annual and monthly temperatures; western associations were separated from eastern ones in terms of annual and seasonal precipitation gradients. Discriminant analysis was a good technique to explore climatic gradients not shown by other general ordination or classification methods.
Keywords: Bioclimatic indices; climate; Continentality; Discriminant analysis; Summer aridity; Water availability

Climatic discrimination of Mediterranean broad-leaved sclerophyllous and deciduous forests in central Spain - Gavilán, Rosario; Fernández-González, Federico (Journal of Vegetation Science, 1997)
Abstract. Climatic differences between three types of deciduous (Quercus pyrenaica) and three types of sclerophyllous (Quercus rotundifolia) Mediterranean forests in the Spanish Sistema Central were analyzed by means of Canonical Discriminant Analysis and Jancey's Discriminant Analysis, applied in successive steps to data from 252 meteorological stations. Climatic data included temperature and precipitation records as well as bioclimatic indices. Discriminant analysis was applied to broad-leaved sclerophyllous and deciduous forest communities sampled at each meteorological station using phytosociological methods. Annual and seasonal (summer, spring) water availability are the most important factor controlling the distribution of the two physiognomic forest types; southwestern associations of Quercus pyrenaica and Q. rotundifolia differ from their colder homologues by annual and monthly temperatures; western associations were separated from eastern ones in terms of annual and seasonal precipitation gradients. Discriminant analysis was a good technique to explore climatic gradients not shown by other general ordination or classification methods.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Bioclimatic indices; climate; Continentality; Discriminant analysis; Summer aridity; Water availability